The salamander room - Mazer, Anne.; Johnson, Steve, 1960- (New York : Knopf : Distributed by Random House, 1991)
A young boy finds a salamander and thinks of the many things he can do to make a perfect home for it.
Keywords: Salamanders -- Fiction; Ecology -- Fiction